Asymmetric routing detection based on flow records - Hao-liang LAN; Wei DING; Zhen XIA (Tongxin xuebao)
The misconfiguration of border routers may cause asymmetric routing in campus networks which connect to multiple ISP.A method FARD was proposed according to the phenomenon.This method uses TCP connection-oriented transmission characteristics combined with the home IP address,locating the possible asymmetric routing IP address in the network based on the flow records provided by the router.Experiment on the access router flow records from the main pointof CERNET network to demonstrate the proposed method.